Peningkatan Pembelajaran Hukum : Metode dan Strategi Efektif dalam Pendidikan Hukum - M. Iwan Satriawan; Reisa Malida; Chaidir Ali; Rudy Rudy (Pusat Riset dan Inovasi Nasional, 2025)
The objective of this journal article is to present the findings of a dissemination activity concerning effective methods for studying legal science within faculties of law. This initiative responds to the persistent issue of the low quality of law graduates from institutions of higher education in Indonesia. The dissemination of effective learning methods in legal studies reveals that the improvement of campus facilities, paricularly classroom, libraries, and the overall safety of the academic environment must be prioritized alongside the enchancement of teaching staff quality. Such enhacement may be pursued by increasing lecturer’s income, thereby allowing them to concentate solely on reserch and teaching without the burden of administrative duties. Improved lecturer quality is expected to contribute significantly to academic quality of law graduates. This is due to the fundamental principle that effective legal education requires extensive reading, which is facilitated through library devolepment, as well as the frequent practice of procedural law, which necessitates the availibility of a legal laboratory in the form of a moot coourt facility.